The contribution of shared rules to neural information alignment, for the first (A) and second (B) experiment half. - Denise Moerel (9080849) (2025)
All plotting conventions are the same for Fig 5A and 5B. The time-course of information alignment is shown in dark blue. This measure was obtained by collapsing the temporal generalization matrix of dissimilarity matrix correlations between the two individuals in each pair along one time dimension. The shaded area represents the 95% confidence interval. Significant correlations (cluster-corrected p <.05) are shown in dark blue below. The dashed orange line shows the time-course of correlations for same-rules pseudo-pairs, who are randomly matched individuals who independently came up with the same rules. This shows the information alignment that is driven by cognitive processes associated with the same rules, as well as sensory evoked signals. Significant differences between real pairs and same-rules pseudo-pairs (cluster-corrected p <.05) are shown in red below, highlighting the socially induced information alignment that cannot be explained by shared rules alone. Note this is based on 16 pairs (32 participants), who were also included in the same-rules pseudo-pairs. We excluded six pairs because there was no other pair within the same counterbalancing that picked the same categorization rules.